The application of a grammar manual in order to solve common verb- conjugation problems found in the students of the first courses of basic level at Abdón Calderón Military High School of Cuenca during the school year 2008-2009 - Nieves Lucero, Doris Nataly (2009)
To do this research, we have followed a scheme proposed by the Army Polytechnic School Language Department which clearly specifies step by step each detail how to develop a research and obtain the required results which permit us to complete it successfully, without forgetting the unconditional support of my dear tutors. First of all, we selected the subject to be investigated which was not difficult for us, as students, we have had experiences in the English teachinglearning process during our studies at school, besides have practiced at the Department of Languages as a fulfilment of the requirement to obtain the bachelors´ degree in applied linguistics. We found some negative aspects in the development of English classes which gave us a trace to start the first step of our research. Through observation and suggestion of some colleagues and specialists, it was possible to select this interesting subject which would affect the student´s life. Then, it explores the main different methodologies and theories of knowledge that could help to overcome the observed problems. For the theoretical frame, different sources have been consulted, such as specialized books and magazines, as well as internet contents...